Nueva especie de escorpión del género Hadruroides (Scorpiones: Caraboctoninae) de los valles interandinos de Perú - Ochoa, José Antonio (2008)
Hadruroides bustamantei, a new caraboctonid species from inter Andean valleys of central Peru (2600—3289 m) is described. This species is most related to H. mauryi Francke & Soleglad, with which was confused. The new species differs from H. mauryi, by length/width ratio of the male chela and the pigmentation pattern of the tergites, legs and metasomal segments. With the description of H. bustamantei, the number of known species in the genus Hadruroides is elevated to ten.